Comparative Study of Radiology Department in Derna City Before and After COVID-19 and Daniel Disasters (Derna Academy Journal for Applied Sciences, 2025)
Radiology departments play a vital role in emergency response, especially during disasters. In the city of Derna, Libya, the COVID-19 pandemic and Storm Daniel exposed critical gaps in disaster preparedness and response capabilities within radiology units. This study aims to compare the challenges, performance, and readiness of radiology departments in Derna during these two major crises and after the infrastructure governmental support of radiology departments. A descriptive cross-sectional study was conducted using a structured, self-administered questionnaire distributed face-to-face to 80 participants, including radiology staff and students in Derna. Descriptive statistical analysis was used to interpret the results, whereas the governmental support succeeded in restoring physical infrastructure (e.g., buildings, HVAC), enabling basic operations. Yet, the support failed to address systemic issues like staff training, equipment resilience, and safety protocols. Overall departmental performance during disasters was rated poor (mean = 2.32/4), despite adequate infrastructure were functionally restored (mean = 2.93/4).  In conclusion Radiology departments in Derna showed partial readiness for disaster response but significant deficiencies in staff safety, equipment preparedness, and emergency planning persist. The study highlights the urgent need for structured disaster protocols, staff training, investment in portable imaging equipment, and institutional support to ensure radiology services remain functional during future emergencies.